An Optimal Seed Based Compression Algorithm for DNA Sequences. (31st July 2016) - Eric, Pamela Vinitha; Gopalakrishnan, Gopakumar; Karunakaran, Muralikrishnan
Abstract : This paper proposes a seed based lossless compression algorithm to compress a DNA sequence which uses a substitution method that is similar to the LempelZiv compression scheme. The proposed method exploits the repetition structures that are inherent in DNA sequences by creating an offline dictionary which contains all such repeats along with the details of mismatches. By ensuring that only promising mismatches are allowed, the method achieves a compression ratio that is at par or better than the existing lossless DNA sequence compression algorithms.